Removal of toxic heavy metals from river water samples using a porous silica surface modified with a new β-ketoenolic host - Tighadouini, Said; Radi, Smaail; Elidrissi, Abderrahman; Haboubi, Khadija; Bacquet, Maryse; Degoutin, Stéphanie; Zaghrioui, Mustapha; Garcia, Yann (Beilstein Journal of Nanotechnology, 2019)
A new hybrid adsorbent material for the efficient removal of heavy metals from natural real water solutions (Moroccan river water samples) was prepared by the immobilization of a new conjugated β-ketoenol–pyridine–furan ligand onto a silica matrix. The thermodynamical properties including pH, adsorption isotherms, competitive adsorption, selectivity and regeneration were studied to investigate the effect of ketoenol–pyridine–furan–silica (SiNL) on the removal of Zn(II), Pb(II), Cd(II) and Cu(II) from aqueous solutions. An increase in adsorption as a function of pH and fast adsorption was reached within 25 min. The maximum sorption capacities for Zn(II), Pb(II), Cd(II) and Cu(II) were 96.17, 47.07, 48.30 and 32.15 mg·g−1, respectively. Furthermore, the material proved to be very stable – its adsorption capacity remained greater than 98% even after five cycles of adsorption/desorption. Compared to literature results, this material can be considered a high-performing remediation adsorbent for the extraction of Zn(II) from natural real water solution.
Keywords: heavy metals; hybrid materials; β-ketoenol–pyridine–furan ligands; polluted media; porous silica; remediation

(untitled) - Kılıç, M.; Kırbıyık, Ç.; Çepelioğullar, Ö.; Pütün, A. E. (Appl. Surf. Sci., 2013)

(untitled) - Yang, W.; Ding, P.; Zhou, L.; Yu, J.; Chen, X.; Jiao, F. (Appl. Surf. Sci., 2013)

(untitled) - Huang, X.; Chang, X.; He, Q.; Cui, Y.; Zhai, Y.; Jiang, N. (J. Hazard. Mater., 2008)

(untitled) - Li, M.; Li, M.-y.; Feng, C.-g.; Zeng, Q.-x. (Appl. Surf. Sci., 2014)

(untitled) - Najafi, M.; Yousefi, Y.; Rafati, A. A. (Sep. Purif. Technol., 2012)

(untitled) - Dabrowski, A.; Hubicki, Z.; Podkościelny, P.; Robens, E. (Chemosphere, 2004)

(untitled) - Fernane, F.; Mecherri, M. O.; Sharrock, P.; Hadioui, M.; Lounici, H.; Fedoroff, M. (Mater. Charact., 2008)

(untitled) - Misra, R. K.; Jain, S. K.; Khatri, P. K. (J. Hazard. Mater., 2011)

(untitled) - Chan, B. K. C.; Dudeney, A. W. L. (Miner. Eng., 2008)

(untitled) - Mohsen-Nia, M.; Montazeri, P.; Modarress, H. (Desalination, 2007)

(untitled) - Afkhami, A.; Saber-Tehrani, M.; Bagheri, H. (J. Hazard. Mater., 2010)

(untitled) - Wan Ngah, W. S.; Teong, L. C.; Hanafiah, M. A. K. M. (Carbohydr. Polym., 2011)

(untitled) - Sakai, H.; Matsuoka, S.; Zinchenko, A. A.; Murata, S. (Colloids Surf., A, 2009)

(untitled) - Silva, R.; Cadorin, L.; Rubio, J. (Miner. Eng., 2010)

(untitled) - Nataraj, S. K.; Hosamani, K. M.; Aminabhavi, T. M. (Desalination, 2009)

(untitled) - Wu, Z.; He, M.; Guo, X.; Zhou, R. (Sep. Purif. Technol., 2010)

(untitled) - Jha, V. K.; Nagae, M.; Matsuda, M.; Miyake, M. (J. Environ. Manage., 2009)

(untitled) - Abu-Eishah, S. I. (Appl. Clay Sci., 2008)

(untitled) - Ahn, C. K.; Park, D.; Woo, S. H.; Park, J. M. (J. Hazard. Mater., 2009)

(untitled) - Mohan, S.; Gandhimathi, R. (J. Hazard. Mater., 2009)

(untitled) - Brown, P. A.; Gill, S. A.; Allen, S. J. (Water Res., 2000)

(untitled) - Ahluwalia, S. S.; Goyal, D. (Bioresour. Technol., 2007)

(untitled) - Sud, D.; Mahajan, G.; Kaur, M. (Bioresour. Technol., 2008)

(untitled) - Pérez-Quintanilla, D.; del Hierro, I.; Fajardo, M.; Sierra, I. (Microporous Mesoporous Mater., 2006)

(untitled) - Wang, M.; Qu, R.; Sun, C.; Yin, P.; Chen, H. (Chem. Eng. J., 2013)

(untitled) - Zhao, J.; Niu, Y.; Ren, B.; Chen, H.; Zhang, S.; Jin, J.; Zhang, Y. (Chem. Eng. J., 2018)

(untitled) - Ge, S.; Geng, W.; He, X.; Zhao, J.; Zhou, B.; Duan, L.; Wu, Y.; Zhang, Q. (Colloids Surf., A, 2018)

(untitled) - Cashin, V. B.; Eldridge, D. S.; Yu, A.; Zhao, D. (Environ. Sci.: Water Res. Technol., 2018)

(untitled) - Zhang, A.; Chen, C.; Ji, Y.; Liu, S.; Guo, S. (J. Chem. Eng. Data, 2018)

(untitled) - Zhang, P.; Niu, Y.; Qiao, W.; Xue, Z.; Bai, L.; Chen, H. (J. Mol. Liq., 2018)

(untitled) - Nurhajawarsi, N.; Rafi, M.; Syafitri, U. D.; Rohaeti, E. (J. Pure Appl. Chem. Res., 2018)

(untitled) - Biesuz, R.; Santos, M. A.; Nurchi, V. M.; Alberti, G. (New J. Chem., 2018)

(untitled) - Mohammedi, H.; Miloudi, H.; Tayeb, A.; Bertagnolli, C.; Boos, A. (Sep. Purif. Technol., 2019)

(untitled) - Radi, S.; El Abiad, C.; Carvalho, A. P.; Santos, S. M.; Faustino, M. A. F.; Neves, M. G. P. M. S.; Moura, N. M. M. (J. Mater. Chem. A, 2018)

(untitled) - Radi, S.; El Abiad, C.; Moura, N. M. M.; Faustino, M. A. F.; Neves, M. G. P. M. S. (J. Hazard. Mater., 2017)

(untitled) - Tighadouini, S.; Radi, S.; Anannaz, M.; Bacquet, M.; Degoutin, S.; Tillard, M.; Eddike, D.; Amhamdi, H.; Garcia, Y. (New J. Chem., 2018)

(untitled) - Radi, S.; Tighadouini, S.; Bacquet, M.; Degoutin, S.; Janus, L.; Mabkhot, Y. N. (RSC Adv., 2016)

(untitled) - Radi, S.; Tighadouini, S.; Toubi, Y.; Bacquet, M. (J. Hazard. Mater., 2011)

(untitled) - Tighadouini, S.; Radi, S.; Bacquet, M.; Dacquin, J.-P.; Mabkhot, Y. N.; Jodeh, S.; Warad, I.; Zaghrioui, M. (Sep. Sci. Technol., 2015)

(untitled) - Radi, S.; Toubi, Y.; Bacquet, M.; Degoutin, S.; Mabkhot, Y. N.; Garcia, Y. (RSC Adv., 2016)

(untitled) - Hui, Y.-Y.; Shu, H.-M.; Hu, H.-M.; Song, J.; Yao, H.-L.; Yang, X.-L.; Wu, Q.-R.; Yang, M.-L.; Xue, G.-L. (Inorg. Chim. Acta, 2010)

(untitled) - Verma, P.; Juneja, H. (Int. J. ChemTech Res., 2012)

(untitled) - Nicole, L.; Boissière, C.; Grosso, D.; Hesemann, P.; Moreau, J.; Sanchez, C. (Chem. Commun., 2004)

(untitled) - Tighadouini, S.; Radi, S.; Bacquet, M.; Degoutin, S.; Zaghrioui, M.; Jodeh, S.; Warad, I. (Sep. Sci. Technol., 2017)

(untitled) - Radi, S.; Tighadouini, S.; Bacquet, M.; Degoutin, S.; Garcia, Y. (Anal. Methods, 2016)

(untitled) - Radi, S.; Tighadouini, S.; Bacquet, M.; Degoutin, S.; Dacquin, J.-P.; Eddike, D.; Tillard, M.; Mabkhot, Y. (Molecules, 2016)

(untitled) - Radi, S.; Tighadouini, S.; Bacquet, M.; Degoutin, S.; Revel, B.; Zaghrioui, M. (J. Environ. Chem. Eng., 2015)

(untitled) - Radi, S.; Tighadouini, S.; El Massaoudi, M.; Bacquet, M.; Degoutin, S.; Revel, B.; Mabkhot, Y. N. (J. Chem. Eng. Data, 2015)

(untitled) - Radi, S.; Tighadouini, S.; Feron, O.; Riant, O.; Bouakka, M.; Benabbes, R.; Mabkhot, Y. (Molecules, 2015)

(untitled) - Arakaki, L. N. H.; Filha, V. L. S. A.; Germano, A. F. S.; Santos, S. S. G.; Fonseca, M. G.; Sousa, K. S.; Espínola, J. G. P.; Arakaki, T. (Thermochim. Acta, 2013)

(untitled) - Dai, B.; Cao, M.; Fang, G.; Liu, B.; Dong, X.; Pan, M.; Wang, S. (J. Hazard. Mater., 2012)

(untitled) - Pérez-Quintanilla, D.; Hierro, I. d.; Fajardo, M.; Sierra, I. (J. Hazard. Mater., 2006)

(untitled) - Yin, P.; Tian, Y.; Wang, Z.; Qu, R.; Liu, X.; Xu, Q.; Tang, Q. (Mater. Chem. Phys., 2011)

(untitled) - Brunauer, S.; Emmett, P. H.; Teller, E. (J. Am. Chem. Soc., 1938)

(untitled) - Sharma, R. K.; Pandey, A.; Gulati, S.; Adholeya, A. (J. Hazard. Mater., 2012)

(untitled) - Iqbal, S.; Yun, J.-I. (Microporous Mesoporous Mater., 2017)

(untitled) - Banerjee, I. A.; Yu, L.; Matsui, H. (Proc. Natl. Acad. Sci. U. S. A., 2003)

(untitled) - Radi, S.; El Massaoudi, M.; Bacquet, M.; Degoutin, S.; Adarsh, N. N.; Robeyns, K.; Garcia, Y. (Inorg. Chem. Front., 2017)

(untitled) - Vojoudi, H.; Badiei, A.; Bahar, S.; Mohammadi Ziarani, G.; Faridbod, F.; Ganjali, M. R. (J. Magn. Magn. Mater., 2017)

(untitled) - Largitte, L.; Pasquier, R. (Chem. Eng. Res. Des., 2016)

(untitled) - Gündoğan, R.; Acemioğlu, B.; Alma, M. H. (J. Colloid Interface Sci., 2004)

(untitled) - Ho, Y. S.; McKay, G. (Process Biochem. (Oxford, U. K.), 1999)

(untitled) - Zheng, H.; Liu, D.; Zheng, Y.; Liang, S.; Liu, Z. (J. Hazard. Mater., 2009)

(untitled) - Foo, K. Y.; Hameed, B. H. (Chem. Eng. J., 2010)

(untitled) - Krishni, R. R.; Foo, K. Y.; Hameed, B. H. (Desalin. Water Treat., 2014)

(untitled) - Limousin, G.; Gaudet, J.-P.; Charlet, L.; Szenknect, S.; Barthès, V.; Krimissa, M. (Appl. Geochem., 2007)

(untitled) - Cui, L.; Wang, Y.; Gao, L.; Hu, L.; Yan, L.; Wei, Q.; Du, B. (Chem. Eng. J., 2015)

(untitled) - Giardina, A.; Larson, S. F.; Wisner, B.; Wheeler, J.; Chao, M. (Environ. Toxicol. Chem., 2009)

(untitled) - Plum, L. M.; Rink, L.; Haase, H. (Int. J. Environ. Res. Public Health, 2010)

(untitled) - Dumoulin, D.; Billon, G.; Proix, N.; Frérot, H.; Pauwels, M.; Saumitou-Laprade, P. (J. Geochem. Explor., 2017)

(untitled) - Smouni, A.; Ater, M.; Auguy, F.; Laplaze, L.; El Mzibri, M.; Berhada, F.; Filali-Maltouf, A.; Doumas, P. (Cah. Agric., 2010)

(untitled) - Xie, F.; Lin, X.; Wu, X.; Xie, Z. (Talanta, 2008)

(untitled) - Dias Filho, N. L.; Costa, R. M.; Marangoni, F. (Colloids Surf., A, 2008)

(untitled) - Radi, S.; Attayibat, A.; Lekchiri, Y.; Ramdani, A.; Bacquet, M. (Mater. Chem. Phys., 2008)

(untitled) - Goswami, A.; Singh, A. K. (Anal. Chim. Acta, 2002)

(untitled) - Kocjan, R. (Microchim. Acta, 1999)

(untitled) - Zaporozhets, O.; Petruniock, N.; Sukhan, V. (Talanta, 1999)

(untitled) - Goswami, A.; Singh, A. K. (Anal. Bioanal. Chem., 2002)

(untitled) - Goswami, A.; Singh, A. K. (Talanta, 2002)